A dual target of Plasmepsin IX and X: Unveiling the atomistic superiority of a core chemical scaffold in malaria therapy. Issue 5 (14th November 2018) - Munsamy, Geraldene; Agoni, Clement; Soliman, Mahmoud E. S.
Abstract: Plasmepsin IX and X, members of the prominent aspartic family of proteases whose function were hitherto unknown have only recently been established as key mediators of erythrocyte invasion and egress of the virulent malarial parasite. Inhibitor 49c, a potent antimalarial peptidomimetic inhibitor initially developed to target Plasmepsin II has lately been proven to exhibit potent inhibitory activity against Plasmepsin IX and X. However, the molecular and structural dynamics supporting its inhibitory activity remain inconclusive. Hindering the motion of the flap and hinge region of an aspartic protease remains essential for disabling the catalytic activity of the enzyme. Integrating molecular dynamic simulations coupled with other advanced biocomputational tools, we reveal the enhanced structural mechanistic competence of 49c in complex with Plasmepsin IX and X relative to Pepstatin. Pepstatin, a known aspartic protease inhibitor which actively hinders the opening and closing of the flap tip and flexible loop and consequently limits access to the catalytic aspartic residues, however, its administration has been related to elevated levels of toxicity. Thermodynamic calculations reveal a higher relative binding free energy associated with Plasmepsin IX and X in complex with 49c as opposed to Pepstatin. A relatively compact and structurally rigid 49c bound complexes sequel into the restriction of the flap and hinge residues by restraining cohesive movement, consequently hindering their "twisting motion" from transpiring. Findings unveil an atomistic perspective into the structural superiority of 49c in complex with Plasmepsin IX and X. Abstract : Hindering the motion of the flap and hinge region of an aspartic protease remains essential for disabling the catalytic activity of the enzyme. A relatively less compact and structurally rigid 49c bound complexes resulted in the restriction of the flap and hinge residues from cohesive movement, consequently hindering their "twisting motion" from transpiring. This study may hasten the search towards the discovery of novel antimalarial drugs amid the current wave of drug resistance.